2011
DOI: 10.1007/s10815-011-9592-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on egg quality

Abstract: Obesity in women is a concern in many countries. This causes numerous health issues; however, this review focuses on the impact of obesity on women's reproduction, and in particular the oocyte. Data from infertility clinics and experimental animal models that address the effects of obesity are presented. Bidirectional communication and metabolic support from the surrounding cumulus cells are critical for oocyte development, and the impact of obesity on these cells is also addressed. Both oocyte maturation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 116 publications
7
94
0
10
Order By: Relevance
“…PI3-K is a regulator of several physiological responses, including cellular proliferation, growth, survival, and glucose metabolism, and is vital for preimplantation embryo survival and development [51,52]. Consistent with our results, some reports have shown that inhibition of PI3-K induces apoptosis in blastocysts [53,54]. The other role of the PI3-K pathway is to regulate glucose uptake mainly via the translocation of glucose transporter proteins to the plasma membrane.…”
Section: Figsupporting
confidence: 91%
“…PI3-K is a regulator of several physiological responses, including cellular proliferation, growth, survival, and glucose metabolism, and is vital for preimplantation embryo survival and development [51,52]. Consistent with our results, some reports have shown that inhibition of PI3-K induces apoptosis in blastocysts [53,54]. The other role of the PI3-K pathway is to regulate glucose uptake mainly via the translocation of glucose transporter proteins to the plasma membrane.…”
Section: Figsupporting
confidence: 91%
“…Animal studies have indicated that obesity significantly impacts oocyte quality [22][23][24][25]. Researchers have used a murine model of mice fed a high-fat diet (HFD) to mimic the effects of obesity and metabolic dysfunction in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that Glut1, Glut3 and Glut4 have increased ovarian expression in daughters of HFD fed fathers, indicating a potential increase in glucose transport in ovarian cells. This may impair oocyte quality as previous studies demonstrate high glucose environments (e.g., diabetic mouse models) impair oocyte quality and development, presumably by altering the glucose levels in the follicular environment [47][48][49]. Moreover, elevated concentrations of glucose in the uterus are associated with poor oocyte developmental competence in vitro [50].…”
Section: Discussionmentioning
confidence: 99%